Soil acidity amelioration improves N and C cycles in the short term in a system with soybean followed by maize-guinea grass intercropping - Barcelos, Jéssica Pigatto de Queiroz [UNESP]; de Souza, Murilo [UNESP]; Nascimento, Carlos Antonio Costa do [UNESP]; Rosolem, Ciro Antonio [UNESP] (Elsevier, 2022)
Lime application has been associated with N and C losses from agricultural systems through NO3– leaching, N2O and CO2 emissions. However, we hypothesized that in an intensive crop system where soybean is grown in rotation with maize intercropped with a forage grass, liming associated with the application of gypsum to ameliorate the subsoil, and N fertilization increase soil N and C by improving root and crop growth. To evaluate the interaction of lime, gypsum and N fertilizer on soil and N and C partial balances, an experiment was carried out under no-till, where soybean was grown in rotation with maize intercropped with Guinea grass (Megathyrsus maximus cv Tanzânia) as relay crop. Lime and gypsum were applied before soybean planting in October 2016 and October 2017. Two N rates (0 and 160 kg ha−1 yr−1 of N as ammonium sulphate) were applied to maize annually. Outputs through N-NO3– leaching, N-N2O emission and N-NH3 volatilization did not exceed 30 kg ha−1 of N in two years. The N exported in grains consisted in 96% of the N output and was greater with fertilizer and lime. Soil acidity amelioration and N-fertilization favoured soil C fixation with high plant biomass production (C in plant residue, roots, and grains), while soil C-CO2 emission was not affected, and soil C increased. Although the partial N balance was negative, there was an increase in soil N, probably due to biological N fixation by soybean, which was not considered in the partial balance. We concluded that lime and gypsum application, along with an adequate N fertilization, to a tropical highly-weathered soil with soybean cropped in rotation with maize-guinea grass intercropping benefit N and C cycles and the environment in the short-term, increasing soil N and C stocks and reducing GHG emitted to the atmosphere.
Keywords: Ammonium sulphate; Conservative system; Greenhouse gas emission; Gypsum; Liming